Have immigrant children been left behind in COVID-19 testing rates? – A quantitative study in the Lisbon metropolitan area between march 2020 and may 2023 - Alves, Iolanda B.; Panunzi, Silvia; Silva, António C.; Loesch, Regina B. R.; Pereira, Sofia C. R.; Martins, M. Rosário O. (Frontiers in Public Health, 2024)
Immigrant children often encounter additional barriers in accessing health care than their peers. However, there is a lack of evidence globally regarding how migrant status may have affected access to COVID-19 testing during the pandemic. This study aimed to analyze migrant status as a determinant of COVID-19 testing rates among children in the Lisbon metropolitan area, Portugal. This cross-sequential study included 722 children aged 2–8 years (47% non-immigrants; 53% immigrants). We collected data from a national surveillance system on laboratory-confirmed COVID-19 tests conducted between March 2020 and May 2023 and assessed whether children were ever tested for COVID-19 and testing frequency. We employed robust and standard Poisson regression models to estimate Adjusted Prevalence Ratios and Relative Risks with 95% confidence intervals. A total of 637 tests were performed. Immigrant children had lower testing rates (53% vs. 48%) and fewer tests per child (median: 2 vs. 3). Moreover, they were 17% less likely to be ever tested (PR = 0.83, 95% CI: 0.76–0.89) and performed 26% fewer tests (RR = 0.74, 95% CI: 0.67–0.82) compared to non-immigrant children. Caregiver’s age, education, employment status, child’s birth weight, and perceived health status were associated factors. Our findings suggest that the COVID-19 pandemic has left immigrant children somewhat behind. We conclude that specific interventions targeting vulnerable populations, such as immigrant children, are needed in future health crises.